It's Not About Being Right: Developing Argument Through Debate. (March 2020) - Malloy, Jacquelynn A.; Tracy, Kelly N.; Scales, Roya Q.; Menickelli, Kristin; Scales, W. David
This research sought to develop argument as a problem-solving process by adding debate to social studies instruction with three groups of fifth-grade students. This design-based research (DBR) reports on the ways that instruction was refined across three topical units to develop argumentative agency and a critical participatory literacy. Students addressed current issues extended from historical events and engaged in issues collaboratively through debates, then individually in their writing. DBR approaches afforded a description of the factors that enhanced and inhibited argument development across the debate cycles and chronicled the modifications that were put in place to refine the instruction. A retrospective analysis led to pedagogical assertions that illuminate what was learned about the interrelationship of oral and written argument and the instructional refinements that were required to support arguments as a means of solving problems.